Laurence-Moon-Bardet-Biedl Syndrome: A case report - Md. Mozammel Haque; Kamrunnaher Shultana; Tahmina Binte Matin; Md. Shohidul Islam Khan; Abdullah Al Baki (Paediatrica Indonesiana, 2019)
Laurence-Moon-Bardet-Beidl syndrome is a rare ciliopathic and pleiotropic human autosomal recessive genetic disorder.1 In 1886, Laurence and Moon explained a case of a 7-year-old female with rod-cone dystrophy, hypogenitalism, mental retardation, obesity, and polydactyly. In 1920, Bardet described a 4-year-old female patient presented with rod-cone dystrophy, obesity, polydactyly (11 toes), and mental retardation.1 Two years after Bardet's report, Biedl highlighted the complete scenario of clinical signs which includes skull abnormalities, anal atresia, mental deficiency, and gastrointestinal conflicts.1 Since these discoveries, symptoms such as obesity, hypogonadism, retinal pigment defects, psychological hindrance, and polydactylismin in several conditions as combinations, frequently in children with normal parents (cousin marriages) has been termed as Laurence-Moon-Bardet-Biedl syndrome (LMBBS).1